225k views
5 votes
What is -6+x-3 if x=2

2 Answers

6 votes

Answer:

-7

Explanation:


-6+x-3 \\x =2\\\\-6+2-3\\\\\mathrm{Follow\:the\:PEMDAS\:order\:of\:operations}\\\\\mathrm{Add\:and\:subtract\:\left(left\:to\:right\right)}\:\:\\-6+2=-4\\\\=-4-3\\\\=-7

User Ronenz
by
6.3k points
4 votes

Answer:

-7

Explanation:

So we have the expression:


-6+x-3

And we want to evaluate it when x is 2.

So, substitute in 2 for x:


=-6+(2)-3

Add the first two terms:


=-4-3

Subtract:


=-7

And that's our answer :)

User Altenrion
by
5.5k points